Downregulation of mPGES-1 Expression via EGR1 Plays an Important Role in Inhibition of Caffeine on PGE2 Synthesis of HBx(+) Hepatocytes - Yan Ma; Xiaoqian Wang; Nanhong Tang (Hindawi Limited, 2015)
We investigated the mechanism of caffeine in influencing HBx(+) hepatocytes to synthesize PGE2. The inhibitory effect of caffeine on hepatocyte proliferation increased with increasing caffeine concentrations (200-800 μM) and treatment times (1-7 days), which was first observed at the second test time point (caffeine treatment for 4 days). The inhibition of caffeine on the growth of HL7702-HBx and HepG2-HBx cells was most obvious at 800 μM caffeine and at caffeine treatment for 7 days. The PGE2 secretion and the expression of mPGES-1 and EGR1 were downregulated, whereas PPARγ expression was upregulated. The mPGES-1 promoter activity of HBx(+) hepatocytes decreased more significantly than that of HBx(−) hepatocytes. Moreover, the expression of EGR1 and PPARγ changed more significantly in HBx(+) hepatocytes cultured for 12 to 24 hours in the presence of 5 mM caffeine. This limited success may be attributed to caffeine releasing the binding of HBx and PPARγ and furthermore affecting the mPGES-1 expression by EGR1 in HBx(+) hepatocytes. The results indicate that caffeine could effectively reduce PGE2 synthesis in HBx(+) hepatocytes by specifically blocking the PPARγ-EGR1-mPGES-1 pathway, thereby providing a new evidence of molecular biology for the hypothesis that drinking coffee is beneficial to HBV-infected patients.